فه‌لسه‌فه‌ی هونه‌ری هاوچه‌رخ، له ‌دیدگای فه‌لسه‌فه‌ی هاوچه‌رخی شیكاریه‌وه‌، له ساڵی‌ ١٩٤٥ بۆ ٢٠٢٠ - خضر, كارزان احمد (Sulaimani Journal for Humanities, 2022)
The philosophy of contemporary art does not comprise a single theme, nor is it an umbrella which includes all aspects of art. As a result, it has been defined as the most esoteric branch of art. Contemporary art coexists with manifold forms of art, and they all differ from each other fundamentally. Generally speaking, intellectual research aims to describe, explain and expound a theme which has not formerly been explored in the realms of thought or philosophy.